M-mode ultrasound used to detect the onset of deep muscle activity - Dieterich, A.; Pickard, Christine; Deshon, Louise; Strauss, Geoff; Gibson, W.; Davey, Paul; McKay, J. (Elsevier Ltd, 2015)
M-mode ultrasound imaging (US) reflects motion of connective tissue within muscles. As muscle contraction is accompanied by motion of muscle tissue, M-mode US may be used to measure non-invasively the onset of deep muscle activity. Isometric hip abduction was measured on nine healthy subjects in the deep region of the gluteus medius muscle and in gluteus minimus by fine-wire electromyography (EMG) and M-mode US. Following signal transformation with the Teager-Kaiser Energy Operator, EMG and M-mode US onsets of muscle activity were computer-processed. Correlation between log-transformed EMG and M-mode high-energy onsets was higher in gluteus medius (r 0.93) than in gluteus minimus (r 0.86). M-mode high-energy onsets followed EMG onset by median 33 (IQR 53) ms in gluteus medius, and by 17 (IQR 63) ms in gluteus minimus. 4% of gluteus medius and 23% of gluteus minimus M-mode onsets were detected before EMG onset. Using a higher onset threshold reduced the rate of onsets detected before EMG but also prediction accuracy. In voluntary activation, M-mode US high-energy onsets were closely related to EMG-measured onsets, but the time interval between both measures varied. The relationship of electrical and mechanical activation onsets appears to be influenced by modifying factors which may differ between muscles.